2014
DOI: 10.1159/000366177
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Pharmacogenomics: A Value-Based Approach to Pragmatic Decision Making in the Face of Complexity

Abstract: Evidence of the value of pharmacogenomic testing is needed to inform policymakers and clinicians for decision making related to adoption and coverage, and to facilitate prioritization for research and development. Pharmacogenomics has an important role in creating a more efficient healthcare system, and this article addresses how economic evaluation can strategically target evidence gaps for public health priorities with examples from pharmacogenomic medicine. This article begins with a review of the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…By integrating economic assessments into translational research not only can the utility of genomic interventions be determined, but the relative value of such interventions can be assessed to inform health care decision-makers. Expanding single-country studies of cost-effectiveness to multiple health care systems may help identify key underpinning structural components that promote favorable cost-benefit ratios [80]. Multi-national collaborations will be particularly valuable for examining different systems and models, such as those with one or a few centralized payers that can provide a more unified and systematic examination of the decision-making process.…”
Section: Opportunities For International Collaborationmentioning
confidence: 99%
“…By integrating economic assessments into translational research not only can the utility of genomic interventions be determined, but the relative value of such interventions can be assessed to inform health care decision-makers. Expanding single-country studies of cost-effectiveness to multiple health care systems may help identify key underpinning structural components that promote favorable cost-benefit ratios [80]. Multi-national collaborations will be particularly valuable for examining different systems and models, such as those with one or a few centralized payers that can provide a more unified and systematic examination of the decision-making process.…”
Section: Opportunities For International Collaborationmentioning
confidence: 99%
“…The real cost-effectiveness of involving genomics in medicine is as yet unknown apart from some rather limited studies in pharmacogenomics and hereditary cancer syndromes. Although it is vital to perform cost-effectiveness analyses for the implementation of genomic medicine in developing countries, there are only a handful of such studies reported in the literature [Snyder et al, 2014]. Realizing cost-effectiveness would be a crucial step towards convincing policy makers of the utility of genomics in healthcare as a means to reduce the overall treatment costs, as well as to reduce the overall burden and minimize consequences of disease at the national level [Payne and Shabaruddin, 2010].…”
Section: Economic Evaluation In Genomic Medicine Working Groupmentioning
confidence: 99%
“…This is further highlighted by the fact that many interviewed expert stakeholders disagreed about the role of clinicians [4]. Some stakeholders reported that clinicians are most reluctant to adopt companion diagnostics even when funding is guaranteed, whereas others reported that clinicians' adoption is not a barrier to access at all [39]. Whichever, close links between pathologists and clinicians help to increase clinicians' awareness about the kind of tests available and how these are appropriately used and interpreted.…”
Section: Incentives For Genomic Medicinementioning
confidence: 99%